Voltage and Frequecy Effect to Characteristic and Amount of Microorganism of Starfruit Extract (Averrhoa carambola L) Using Pulsed Electric Field (PEF) - Sumarlan, Sumardi Hadi; Liani, Riska Dwi April; Yulianingsih, Rini; Indriani, Dina Wahyu (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Fruit extract is one of the food commodities with high demand. Good processing will increase consumption level and sell price. There are two methods for food processing, thermal processing and nonthermal processing. Nonthermal processing method using Pulsed Electric Field (PEF) is one of the alternative way which can be used to decrease amount of microbs and keep fruit extractâ€™s nutritions. Bangkok Red Starfruits varieties which has good taste and smooth texture has be come a good raw material in starfruit extract manufacture. Voltage variations in this research are 20 kV, 30 kV and 40 kV, with frequency variations which are 10, 20, 30 and 40 kHz. Testing results of this research using PEF showed that initial amount of microbe are 1300 CFU/mL can decrease effectively. Minimal decrease happened at voltage 40 kV and 30 kHz of frequency reached 130 CFU/mL. Maximal decrease happened at 40 kV of voltage reached 85.19%. with amount of microbs 1.925 x 103 CFU/mL. Lethal rates per second is 21.3 CFU/mL at 40 kV of voltage. Characteristic result testing has not significant diferences, there are range of pH at 3.09-3.24, Density 1.047-1.076 gram/cm3 , Total Suspended Solid at 14.5-15.6 %Brix, Viscosity at 7-9 Cp, Vitamin C contained at 11.66-16.97 mg/100 mL, and range of color, there are brightness level at 27.8-29.3, red level at 6.7-7.3 , and yellow level 6.8-7.9 .Keywords: Bangkok Red Starfruit, Pulsed Electric, Microbe Amounth.Â